Effect of Team Based Support on Organizational Commitment in Insurance Companies in Uasin Gishu County, Kenya - Mandago, Dr. Rael; Kipcumba , Johnstone Tarus (European Journal of Human Resource, 2024)
Purpose: To assess the effect of team based support on organizational commitment in insurance companies in Uasin Gishu County, Kenya Materials and Methods: In a bid to effectively achieve these objectives, the study adopted a descriptive research design based on samples drawn from across the insurance companies in Uasin Gishu County. The target population was 754 insurance companies’ employees. A two-stage sampling technique was adopted where stratified random sampling was used to select the insurance companies after which simple random sampling was used to select respondents within the insurance companies. The study used the Krejcie and Morgan table (1970) to calculate the sample size which was 260 respondents from the target population of 754 respondents. The sample size was distributed proportionally to the insurance companies according to Neyman’s allocation formula to maximize survey precision. Data was collected by use of self-administered questionnaires which was tested for validity and reliability after piloting 26 questionnaires at Kisumu city insurance companies. Data was analyzed by use of both inferential and descriptive statistics using SPSS version 25. Findings: There is a significant effect of team-based support on Organizational Commitment in insurance companies in Uasin Gishu County, Kenya ((b=.108, p=0.004). These findnings are based on the social exchange theory. Implications to Theory, Practice and Policy: The organization should invest in team-based support amongst employees. The insurance companies should ensure that they strengthen their policy frameworks which recognize and enhance team-based support within various domains of their operations. The team should have clarity of purpose and concern for others built on mutual trust for cohesiveness to perpetuate organizational commitment. Besides as a team the employees should use their diversity of skills and Knowledge to develop diverse talents for optimal organizational commitment.